A feminist server stack: co-designing feminist web servers to reimagine Internet futures. Issue 1 (2nd January 2022) - Mauro-Flude, Nancy; Akama, Yoko
ABSTRACT: In this article, we reimagine the Internet as a feminist cosmos called a Feminist Server Stack. By scrutinising how webserver infrastructure is normalised based on imperial conventions and distorted knowledge systems, we suggest alternatives. This embrace of 'post-patriarchal futures' (Bardzel 2019, 20) offers counter perspectives on how we may holistically embody the Internet as a situated ecology. When experiencing the Internet materiality, it leads us to imagine beyond the known and possible. We focus on enchanting affirmations and tacit hands-on computational methods from the frontiers of feminist digital literacy and server communities. These acts make visible the seams and fissures of concealed undercurrents and schemata of infrastructures. The findings reveal utterly different relationships between webserver providers and clients. Drawing from extensive fieldwork and observational analysis, we show how the choreography of happenings is seeding the ground for participatively co-designing the transfiguration of planetary computing into one that is scalable, visceral, and restorative. We welcome these nascent pathways to guide us to an enigmatic realm upon which theories of co-design could dance in communion with a realm that is to-come.